A leitura da paisagem geográfica: Uma proposta metodológica para o ensino fundamental II - Pichiteli, Milaine Aparecida (2018)
The landscape concept, as one of the concepts that makes up the basis of the study of Geography as Science, is also the guideline of Geography at School, presenting didactic possibilities that allow the student to contact with the ordinary reality. In this context, the present research had the objective to present based on the assumptions of the Geography?s didactic, a methodological solution that contributes with the discipline, enabling the student to analyze and understand its contents, through the reading and analysis of the landscape. The research was based on the collaborative approach, therefore, two elementary teachers were invited to contribute during all stages of development of the methodological proposal, as well as the implementation and analysis of the results. It was pursued through this collaboration to give solid foundation to the methodological proposal, through Pedagogical Content Knowledge (PCK) and in particular Geographic Pedagogical Knowledge (GPK) developed through the extensive experience of the training course of the invited teachers. The proposal was implemented in two schools of the Regional Education Center of Maringá, Paraná, one of them, in the main city of the center ? Maringá ?, which is a 6th grade class, and other, in Sarandi city, which is a 7th grade class. Through the analysis of the collected information through the general implementation, as well as the statements of the students contained in the Landscape Reading Guides, this guide developed as a didactic contribution of the methodological proposal, it was possible to active results that demonstrate that the present proposal, structured taking into account a conceptual deepening, together with a direct and indirect reading of the landscape, contributing with the development of the concept of landscape as well as in the apprehension of geographical contents by the students, favoring also in its formation while critical and participatory citizens in the society